Tales of un-knowing : therapeutic encounters from an existential perspective - Spinelli, Ernesto (Ross-on Wye, England : PCCS Books, 1997)
In Tales of Un-Knowing, Ernesto Spinelli, a leading exponent of existential therapy, presents a therapeutic approach that has proven highly effective in assisting troubled individuals in confronting the problems of everyday life. Tales of Un-Knowing presents the lives of eight individuals whose experiences illuminate a variety of dilemmas and anxieties that most of us encounter at different points in our lives. Among the people we meet are Mr. Jones, who refused to grow old gracefully, Amanda, who feared that she was only loved for her body, and Jim, an octogenarian who lived simultaneously in the present and in the past. We also meet Giles, whose obsessive identification with Einstein led him to theorize about his sex until it became a "living mathematics" full of enthralling permutations and combinations. In the course of the book Spinelli tackles head on the last great taboo of therapeutic practice - sexual attraction between therapist and client.
Includes bibliographical references.
Keywords: Existential psychotherapy -- Case studies